2020
DOI: 10.1108/jeas-08-2018-0094
|View full text |Cite
|
Sign up to set email alerts
|

Adopting the international financial reporting standard for small and medium-sized entities in Saudi Arabia

Abstract: PurposeThe paper investigates attitudes towards and perceptions of the adoption of the International Financial Reporting Standard (IFRS) for small and medium-sized entities (SMEs) in Saudi Arabia, immediately before and during the period of adoption.Design/methodology/approachThe study adopts an interpretive approach, using a new institutional theory framework, drawing on concepts of institutional isomorphism and institutional logics. Research was undertaken using extensive interviews of business owners and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
1
14
0
1
Order By: Relevance
“…In addition, it is also driven by the perception of the benefits received by other MSMEs adopting Islamic finance or by other well-known MSMEs, even without certain success. These results are in line with Chathurangani and Hemathilake (2019), Bakr and Napier (2020), Sadress et al (2019), andTalib et al (2020).…”
Section: Figure 2 Structural Model and Parameter Estimation Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, it is also driven by the perception of the benefits received by other MSMEs adopting Islamic finance or by other well-known MSMEs, even without certain success. These results are in line with Chathurangani and Hemathilake (2019), Bakr and Napier (2020), Sadress et al (2019), andTalib et al (2020).…”
Section: Figure 2 Structural Model and Parameter Estimation Resultssupporting
confidence: 91%
“…This situation will encourage MSMEs to carry out a mimetic process by imitating MSMEs or other organizations to meet the needs of these financial products and services. Mimetic mechanisms have also been shown to have a significant role in some adoption behaviors, both in the context of MSMEs as in a study by Bakr and Napier (2020), Sadress et al (2019), Caldera et al (2019), Masocha and Fatoki (2018), and Raghavan et al (2018), as well as in the context of Islamic business and finance, as researched by Bashir (2019a) and Talib et al (2020). Therefore, the following hypothesis could be formulated:…”
Section: H1mentioning
confidence: 96%
“…Negative effects of the usage of accounting software are increased cost, lack of education on the benefits of the usage and lack of knowledgeable personnel. Ibrahim et al (2020) and Pulakanam and Suraweera (2010) analyzed and found that small businesses, while implementing small business accounting software, face many barriers, such as nonuser-friendly and non-availability of software vendors' support and guidance (Bakr, 2020). Ashrafi and Murtaza (2008) in their study provided that only a very a smaller number of SMEs in Oman are aware of the available accounting software and its adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mimetic isomorphism refers to the imitation of what institutions consider successful practices of other institutions. On the other hand, “normative” isomorphism indicates that the institution follows what is widely seen to be “best practice” and followed such as IFRS and US GAAP ( Bakr and Napier, 2020 ). IFRS adoption is also justified by signaling theory, where companies tend to signal to investors by adopting extra mechanisms and additional information disclosures ( Barth et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%